2016
DOI: 10.1016/j.eururo.2015.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Surgery Versus Radiotherapy for Clinically-localized Prostate Cancer: A Systematic Review and Meta-analysis

Abstract: We reviewed available studies assessing mortality after prostate cancer treatment with surgery or radiotherapy. While the studies used have a potential for bias due to their observational design, we demonstrated consistently higher mortality for patients treated with radiotherapy rather than surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
182
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(197 citation statements)
references
References 28 publications
8
182
4
3
Order By: Relevance
“…Of note, patients who undergo radiotherapy tend to be older and have greater comorbidity. Further, as shown in the present study and supported by others, 8 patients are more likely to receive salvage therapy after radical prostatectomy than radiotherapy and, when offered, salvage therapy after radiotherapy is typically in the form of androgen-deprivation therapy. With high-quality, randomized trials comparing surgery to radiotherapy unlikely to be available in the future, 9,10 interpretation of available observational results, regardless of the endpoints evaluated, must be framed in the context of an individual patient.…”
supporting
confidence: 67%
See 1 more Smart Citation
“…Of note, patients who undergo radiotherapy tend to be older and have greater comorbidity. Further, as shown in the present study and supported by others, 8 patients are more likely to receive salvage therapy after radical prostatectomy than radiotherapy and, when offered, salvage therapy after radiotherapy is typically in the form of androgen-deprivation therapy. With high-quality, randomized trials comparing surgery to radiotherapy unlikely to be available in the future, 9,10 interpretation of available observational results, regardless of the endpoints evaluated, must be framed in the context of an individual patient.…”
supporting
confidence: 67%
“…A recent systematic review of observational data compared these endpoints for radical prostatectomy and radiotherapy. 8 Overall and prostate cancer-specific mortality favoured radical prostatectomy, although the most common non-surgical modality was external beam radiotherapy. On subgroup analysis, however, both mortality outcomes favoured surgery over brachytherapy.…”
mentioning
confidence: 99%
“…Unlike localized prostate cancer (PC) for which recent studies have suggested that radical prostatectomy (RP) may provide superior long-term outcomes compared to radiotherapy (RT) [1] , RT is still considered the treatment of choice in locally advanced PC stages [2] .…”
Section: Introductionmentioning
confidence: 99%
“…Due to insufficient power and small series (89 patients) no conclusion could be drawn about the efficacy. Nonetheless, some observational data suggest that outcomes with RP lead to better overall and cancer-specific survival than RT [108112]. Wallis and colleagues recently published a meta-analysis comparing RP with EBRT or BT [108].…”
Section: Rt Compared To Surgerymentioning
confidence: 99%